The Conduct of Monetary Policy in the Major industrial Countries : Instruments and Operations Procedures: Occa Paper No.70. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1990)
This paper discusses instruments and operating procedures of the conduct of monetary policy in the major industrial countries. The exchange rate mechanism of the European Monetary System (EMS) provides clear evidence of the role of exchange rates in influencing monetary policy; the commitment of EMS participants to maintain their exchange rates within agreed limits has often led them to undertake policy measures aimed at exchange rate objectives. The procedures for implementing monetary policy in the five countries examined here exhibit numerous common features; the dissimilarities that exist do not appear to be fundamental, but rather are attributable primarily to differences in institutional conditions. This paper describes the procedures employed by these monetary authorities so that changes in policy stances can be identified.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet